An Investigation on Measles Out Break in Navagam Village of Surendra Nagar District of Gujarat, India in 2008 - Oza, Jaydip R; Chavada, Mallika; Prajapati, Jagruti (National Journal of Community Medicine, 2011)
Background: An outbreak of measles was reported from a Navagam village of Surendranagar District, Gujarat, in July 2008. The present study was conducted to investigate and assess various epidemiological features associated with measles outbreak. Methods: A community based cohort study was carried out in Navagam village of Surendranagar district during month of June 2008. Suspected cases were detected through active case finding in the community. Children <15 years of age with symptoms of Fever and rash and cough or coryza or conjunctivitis (Red eye) in Navagam area of Kharaghoda PHC, Surendranagar district from 1st June, 2008 to 1st August, 2008 were identified as case in present outbreak. Blood samples were taken for IgM antibody detection. Results: The study covered 326 houses having 777children. An overall attack rate 11.17% was almost equal in both male & female. Among measles cases, 45 (49.45%) had post measles complications. As much as 69.23% children with measles had received measles vaccination in the past. Out of 11 blood samples, 10 were positive for IgM antibody. Conclusions: The outbreaks occurred due to poor vaccine coverage levels and an inefficient surveillance system which failed to generate early warning signals.